Teachers' Digital Literacy in Contextual PAI Learning Based on Religious Moderation in Bengkulu Province - Satrisno, Hengki; Efendi, Sutrian (Jurnal Ilmiah Syi'ar, 2023)
This research describes the state of teachers' digital literacy in contextual PAI learning based on religious moderation in Bengkulu Province as well as what are the supporting and inhibiting factors in implementing literacy for teachers. This research is qualitative research which is included in the field research category with data collection methods through observation, documentation and interviews. The results of the research show that the digital literacy of contextual PAI teachers based on religious moderation in Bengkulu province can be considered quite good because in learning teachers have used a lot of videos, social media, digital learning games and digital discussion forums in every lesson. At the same time, there are supporting and inhibiting factors for teachers in contextual PAI learning based on religious moderation, namely: (1) Supporting factors: adequate facilities and infrastructure, skills and competencies of PAI teachers, as well as the existence of government policies and support (2) Meanwhile, the inhibiting factors are : a). Internal factors, namely the teacher's inability to keep up with technological developments; b) External factors, namely unequal distribution of internet access in the regions, lack of training and government support for teachers and environmental literacy which is still low.